Does different workload affect horses’ behaviour? - Mohd Yazid, Nurfarahin (2017)
Horses are social animals and often need optimum environment to maintain its performance. This experiment consists of 18 thoroughbred horses consisting of 3 females and 15 geldings. These horses were then put into 3 groups based on their workload which are endurance group, riding school group and ex-race horses. These for each group, the horses are observed for two weeks or 14 days consecutively and the behaviours performed were marked on the datasheet and data was collected. For every 10 minutes, the behaviour performed by each horses was observed carefully. The experiment requires a ten hour observation from 8 AM to 6 PM.